2018
DOI: 10.1016/j.ymthe.2017.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Self-Transducible Bimodal PDX1-FOXP3 Protein Lifts Insulin Secretion and Curbs Autoimmunity, Boosting Tregs in Type 1 Diabetic Mice

Abstract: Type 1 diabetes (T1D) is characterized by massive destruction of insulin-producing β cells by autoreactive T lymphocytes, arising via defective immune tolerance. Therefore, effective anti-T1D therapeutics should combine autoimmunity-preventing and insulin production-restoring properties. We constructed a cell-permeable PDX1-FOXP3-TAT fusion protein (FP) composed of two transcription factors: forkhead box P3 (FOXP3), the master regulator of differentiation and functioning of self-tolerance-promoting Tregs, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
0
2
0
1
Order By: Relevance
“…Each independent sample was normalized to the level of Gapdh , as this gene was not altered in R6/1 brains 20,23 . The following primer pair sequences were obtained from previous works: Gapdh (5′-CATGGACTGTGGTCATGAGCC-3′, 5′-CTTCACCACCATGGAGAAGGC-3′), Penk (5′-GGCGTGCACACTGGAATGT-3′, 5′-TCCCAGATTTTGAAAGAAGGCA-3′), Plk5 (5′-CACCTGTGTTTGCCTTTCCC-3′, 5′-TTTTGAGGTAAAGGGACAAGGTG-3′), Itpka (5′-TACACTCGGCTTTCGCATTG-3′, 5′-CAAAGACACGGGTCACTTGCT-3′), Rin1 (5′-GCGGCTGCCAGAAGCTAGT-3′, 5′-CCTGGAACATGAGCTCTGAGC-3′), Gabrd (5′-ATTGGAGGTGCTCCTGTGAAT-3′, 5′-CCATGTTTGCCTCTGAGATAT-3′), Pde10a (5′-TAACAATGCGAGTTGCTTCC-3′, 5′-CAGCCACTTTTCCACAGTCTC-3′), Nfya (5′-ACAAGGGACGGTCACTGTGAC-3′, 5′-TTTGGATAGCAGGCACAGAGC-3′), Bcl2 (5′-CACACCTGGATCCAGGATAAC-3′, 5′-GAGAAATCAAACAGAGGTCGCA-3′) 20,23,24 , Gfap (5′-GGACAACTTTGCACAGGACCTC-3′, 5′-TCCAAATCCACACGAGCCA-3′), H2Q7/8/9 (5′-AGGAGCAGAATTACACATGCCA-3′, 5′-CGCCATGTTGGAGAGAGTGTAT-3′) 53 , Arg1 (5′-TGGCTTGCGAGACGTAGAC-3′, 5′-GCTCAGGTGAATCGGCCTTTT-3′) 54 , Bax (5′-TGAAGACAGGGGCCTTTTTG-3′, 5′-AATTCGCCGGAGACACTCG-3′) 55 , Scn4b (5′-CATGGTTTAGTCCTCTGGCTTGG-3′, 5′-CACGGCCCACCACTGTATTG-3′) 56 , Tac1 (5′-ATGAAAATCCTCGTGGCCGT-3′, 5′-GTTCTGCATCGCGCTTCTTT-3′) 57 , and Mbd2 (5′-CCTTAGCAGTTTTGACTTCAGG-3′, 5′-TGGCAATGTTGTGTTCAGGT-3′) 58 . Other sequences were: Hsp90b1 (5′-GATGATCTCCCCCTCAATGTT-3′, 5′-ATATTCGTGCCGAACTCCTTC-3′), Nfyb (5′-GACAGCTACGTGGAGCCTCTG-3′, 5′-AGTCCATCTGTGGCGGAGAC-3′) and Trpc4 (5′-TGAGAAGGAAGCCAGAAAGCTTCG-3′, 5′-CCTTAACATTCTCCTCCGTCAAGCC-3′).…”
Section: Methodsmentioning
confidence: 99%
“…Each independent sample was normalized to the level of Gapdh , as this gene was not altered in R6/1 brains 20,23 . The following primer pair sequences were obtained from previous works: Gapdh (5′-CATGGACTGTGGTCATGAGCC-3′, 5′-CTTCACCACCATGGAGAAGGC-3′), Penk (5′-GGCGTGCACACTGGAATGT-3′, 5′-TCCCAGATTTTGAAAGAAGGCA-3′), Plk5 (5′-CACCTGTGTTTGCCTTTCCC-3′, 5′-TTTTGAGGTAAAGGGACAAGGTG-3′), Itpka (5′-TACACTCGGCTTTCGCATTG-3′, 5′-CAAAGACACGGGTCACTTGCT-3′), Rin1 (5′-GCGGCTGCCAGAAGCTAGT-3′, 5′-CCTGGAACATGAGCTCTGAGC-3′), Gabrd (5′-ATTGGAGGTGCTCCTGTGAAT-3′, 5′-CCATGTTTGCCTCTGAGATAT-3′), Pde10a (5′-TAACAATGCGAGTTGCTTCC-3′, 5′-CAGCCACTTTTCCACAGTCTC-3′), Nfya (5′-ACAAGGGACGGTCACTGTGAC-3′, 5′-TTTGGATAGCAGGCACAGAGC-3′), Bcl2 (5′-CACACCTGGATCCAGGATAAC-3′, 5′-GAGAAATCAAACAGAGGTCGCA-3′) 20,23,24 , Gfap (5′-GGACAACTTTGCACAGGACCTC-3′, 5′-TCCAAATCCACACGAGCCA-3′), H2Q7/8/9 (5′-AGGAGCAGAATTACACATGCCA-3′, 5′-CGCCATGTTGGAGAGAGTGTAT-3′) 53 , Arg1 (5′-TGGCTTGCGAGACGTAGAC-3′, 5′-GCTCAGGTGAATCGGCCTTTT-3′) 54 , Bax (5′-TGAAGACAGGGGCCTTTTTG-3′, 5′-AATTCGCCGGAGACACTCG-3′) 55 , Scn4b (5′-CATGGTTTAGTCCTCTGGCTTGG-3′, 5′-CACGGCCCACCACTGTATTG-3′) 56 , Tac1 (5′-ATGAAAATCCTCGTGGCCGT-3′, 5′-GTTCTGCATCGCGCTTCTTT-3′) 57 , and Mbd2 (5′-CCTTAGCAGTTTTGACTTCAGG-3′, 5′-TGGCAATGTTGTGTTCAGGT-3′) 58 . Other sequences were: Hsp90b1 (5′-GATGATCTCCCCCTCAATGTT-3′, 5′-ATATTCGTGCCGAACTCCTTC-3′), Nfyb (5′-GACAGCTACGTGGAGCCTCTG-3′, 5′-AGTCCATCTGTGGCGGAGAC-3′) and Trpc4 (5′-TGAGAAGGAAGCCAGAAAGCTTCG-3′, 5′-CCTTAACATTCTCCTCCGTCAAGCC-3′).…”
Section: Methodsmentioning
confidence: 99%
“…Several interventions have been developed based on this finding (40, 41). Amatya et al demonstrated the possibility of anti-T1D therapy by constructing a cell-permeable PDX1-FOXP3-TAT fusion protein (FP) to stabilize Tregs for the purpose of anti-autoimmune and insulin production (42). The protein was tested both in vitro and in vivo (nonobese diabetic mouse T1D model).…”
Section: Current Immunotherapy Strategiesmentioning
confidence: 99%
“…2). 20 Contudo, não teve impacto no controlo da glicemia nestes ratinhos. Por fim, apenas existem estudos acerca da administração deste fator em modelos de ratinhos, pelo que estes resultados carecem de corroboração em pessoas com DM1.…”
Section: Alterações Nas Células Treg Na Dm1unclassified